PENGARUH BUKU CERITA DALAM PEMEROLEHAN BAHASA KEDUA PADA ANAK USIA 3 TAHUN - Meta Paramita Nur Azizah (MATAPENA: Jurnal Keilmuan Bahasa, Sastra, dan Pengajarannya, 2020)
Language is a tool that humans use in everyday life. Language acquisition can be divided into two: (a) First language acquisition or commonly referred to as native language, and (b) Second language acquisition. This language acquisition is in Psychocholinistic studies. So to be able to deepen the problem of language acquisition, we are required to deepen psykolinguistic. This journal will discuss the acquisition of a second language acquired through the story book. The story book is commonly read by her mother every night. The method used in this research is dialiog qualitative descriptive method. Keywords: language, psycolinguistic, language acquisition.